Enhanced GP training – the need for change. Issue 1 (January 2013) - Simon, Chantal; Riley, Ben
In April 2012, the Medical Programme Board of Medical Education England approved the RCGP's educational case for extended and enhanced GP training. This article explores the reasons why enhanced GP training is needed and why improved training cannot be achieved without an extension of the duration of training.